Investigating Molecular Interactions of Thyroid Hormone and Androgen Receptors - Zhao, Yi (2023)
Nuclear receptors (NRs) are a large family of ligand regulated transcription factors that play important roles in mammalian physiology. Many NRs function as heterodimer complexes, allowing crosstalk between different ligand signaling pathways. Malfunction of NRs is important in cancer and other diseases. This study focused on a potential interaction between ligand binding domains (LBDs) of Androgen Receptor (AR; residues 647-920) and Thyroid receptor (TRß residues 211-461). The androgen receptor signaling pathway plays an important role in both normal prostate development and prostate cancer progression. Recent studies indicate that expression levels of the thyroid hormone-binding protein ß-crystallin (CRYM) tumors influences tumor progression. This and other evidence suggest a possible interaction between AR and TR signaling, possibly through heterodimeric complexes. As crystal structures were available for monomeric LBDs of both AR and TRß, and a homodimer of the AR, molecular docking experiments were performed using multiple protein docking software (HDOCK, HADDOCK, GRAMM-X, ZDOCK). Cluster analysis then was performed to identify the most stable predicted conformers and to model residues in TRß predicted to participate in binding to AR. The AR:TR interface was predicted to involve residues, F755, W752, Y764, P767 and V770 in AR, which form the AR homodimer interface in the homodimer crystal structure. For TRβ, the binding interface in the predicted model was mainly located in helix 9 and helix 10, which is involved in retinoid X receptor (RXR) binding in TR/RXR heterodimers. The major contributors for heterodimerization with AR were residues, T756, V758, P802, S759, in AR and residues, S207, P384, P419, M423, M430, in TRß. Yeast two hybrid assays successfully detected interaction of AR and TR LBDs, but only in the presence of agonist ligands for both receptors. Moreover, mutation of residues, F755, W752, Y764, P767 and V770 in AR, which form the AR homodimer interface, disrupted interactions with TRβ in yeast. To investigate interactions between AR and TRβ LBDs in mammalian cells, the aim was to generate SPLIT yellow fluorescence protein (YFP) expression vectors for TRß LBD. Difficulties in amplification of TRα1, TRα2 and TRβ1 cDNAs may be linked to GC content in each sequence. The construct TRβ1 LBD -vYFPC156 was generated and sequence validated and was functional in forming ligand dependent interaction with the nuclear receptor interacting domain (NID) of steroid receptor cofactor (SRC1) (construct SRC1 NID - vYFPN155) when co-transfected with in HEK293 cells. However, preliminary attempts to detect AR-TR LBD heterodimers using this assay were not successful and needs to be confirmed in future studies.